Silver nanoparticle toxicity on Artemia parthenogenetica nauplii hatched on axenic tryptic soy agar solid medium - Minh Anh Do; Hoa Thi Dang; Nhinh Thi Doan; Hong Lam Thi Pham; Tuyet Anh Tran; Van Cam Thi Le; Tim Young; Dung Viet Le (Scientific Reports, 2023)
Abstract The use of gnobiotic brine shrimp (Artemia spp.) for ecotoxicology and bacteria-host interaction studies is common. However, requirements for axenic culture and matrix effects of seawater media can be an obstacle. Thus, we investigated the hatching ability of Artemia cysts on a novel sterile Tryptic Soy Agar (TSA) medium. Herein, we demonstrate for the first time that Artemia cysts can hatch on a solid medium without liquid, which offers practical advantages. We further optimized the culture conditions for temperature and salinity and assessed this culture system for toxicity screening of silver nanoparticles (AgNPs) across multiple biological endpoints. Results revealed that maxima hatching (90%) of embryos occurred at 28 °C and without addition of sodium chloride. When capsulated cysts were cultured on TSA solid medium Artemia were negatively impacted by AgNPs at 30–50 mgL−1 in terms of the embryo hatching ratio (47–51%), umbrella- to nauplii-stage transformation ratio (54–57%), and a reduction in nauplii-stage growth (60–85% of normal body length). At 50–100 mgL−1 AgNPs and higher, evidence of damage to lysosomal storage was recorded. At 500 mgL−1 AgNPs, development of the eye was inhibited and locomotory behavior impeded. Our study reveals that this new hatching method has applications in ecotoxicology studies and provides an efficient means to control axenic requirements to produce gnotobiotic brine shrimp.